Perlindungan Hukum Bagi Pembeli Yang Beritikad Baik Terhadap Akta Jual Beli Hak Atas Tanah Yang Tidak Sesuai Dengan Tata Cara Pembuatannya - I Nyoman Suryana (Universitas Mahendradatta, 2020)
The growing of importance meaning of the land to human life today may causes increase of the potential for conflicts or land disputes, to prevent or at least to reduce the potential for conflict or dispute are required legal and orderly system of land administration. Therefore isrequired to transfer land rights to be registered must be proven by deed of PPAT. As authentic documents PPAT deed must meet procedures for making the deed of PPAT as determined by the laws and other rules. Making the deed that is incompatible with how making PPAT deed may pose a risk to the certainty of land rights arising or recorded on the basis of such deed. Based on this background the authors give the title of this thesis, The Legal Consequences of Making the Deed of Sale and Purchase of Land That is Incompatible With PPAT Deed Making Procedures. The aim of this study is to determine the forms, causes and legal consequences of making the deed of sale and purchase of land not in accordance with the procedure making the deed of PPAT. Precriptive specification research in juridical normative law method is used. The data source that is used are primary and secondary data. The data is collected by analyzing law expert theories and also library research that are related.The method of juridical approach used is empirical research with prescriptive specifications and data sources used are primary andsecondary data. Collecting data is done by doing library research and field study and then after the data were analyzed conclusion is by using the method of inductive thinking.Based on this research found that, the legal effect of making the deed of sale and purchase of land not in accordance with procedures for making the deed of PPAT is: PPAT can be dishonorably discharged, PPAT deed degraded the strength of proof becomes deed under hand and third parties may utilize it to its interests